Responsibility for justice - Young, Iris Marion, 1949- (New York ; Oxford : Oxford University Press, 2011)
In 'Responsibility for Justice', Young discusses our responsibilities to address 'structural' injustices in which we - among many - are implicated, but not to blame. Young argues that addressing these structural injustices requires a new model of responsibility, which she calls the 'social connection' model.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Responsibility; Social ethics; Social justice